PROFILE HOME INSTRY RAKIK LOKAN AS FAMILY ECONOMIC DEVELOPMENT IN TANJUNG MEDAN VILLAGE PANCUNG SOAL DISTRICT PESISIR SELATAN REGION - SUSANTI, Dewi; Ahmad, Drs. Ridwan; Thesiwati, SP., M.Si, Aslan Sari (STKIP PGRI Sumbar, 2014)
Â ABSTRACTÂ This study aimed to obtain, analyze and discuss data about home industry Rakik Lokan as Families Economic development in Tanjung Medan Village Pancung Soal District of Pesisir Selatan Region beheading of : 1 ) Availability of raw materials, 2) industrial capital, 3) marketing conditions, 4) industrial labor, 5) business and industry and 6) Constraints experienced industries.This type of research is classified as descriptive. Population was all home industries rakik lokan totaling 10 pieces. Samples were taken with a total sampling technique that is 10 pieces of rakik lokan industry. Collecting data using guided inquiry, statistical analysis used was descriptive using percentage formula.The results showed as follows; 1) Raw materials are always available to rakik lokan industry with very good quality, bought the others from the region itself, depending on the raw material inventory of the weather conditions and the amount of output produced 1000 grains/day, (2) capital resources and capital equipment from of capital itself, a large capital < Rp 1.000.000, is used for wage labor, purchase of production equipment, operational costs and marketing costs, the availability of sufficient capital but capital is no less developed, (3) marketing through intermediaries/orders, production is done in accordance with orders, marketing limited in districts with a motorbike by home industry rakik lokan, (4) labor generally two, and owner of labor, labor day but less labor availability, (5) generally do not wear Processing preservatives, there is no difficulty in processing and no problems in processing and ( 6 ) constraints faced related to marketing is the marketing and narrow region unequal income with expenditure